Ten‐year follow‐up study found that motor‐free intelligence quotient declined in children with mild‐to‐moderate cerebral palsy. (8th July 2022) - Coceski, Monika; Stargatt, Robyn; Sherwell, Sarah; Abu‐Rayya, Hisham M.; Reid, Susan M.; Reddihough, Dinah S.; Wrennall, Jacquie; Hocking, Darren R.
Abstract: Aim: This 10‐year follow‐up study examined cognitive change in a cohort of children with cerebral palsy from preschool to adolescence at the group and individual levels. Methods: The Wechsler Preschool and Primary Scale of Intelligence was administered to 80 children with cerebral palsy (mean = 4 years 6 months, standard deviation = 7 months) at baseline (Time 1). At 10‐year follow‐up (Time 2), 28 adolescents (mean = 14 years 6 months, standard deviation = 9 months) returned for assessment with the Wechsler Intelligence Scale for Children. Motor‐free intelligence quotient (IQ) scores were calculated and paired‐samples t ‐tests and the Reliable Change Index (RCI) were used to investigate change in IQ over time. Results: At the group level, nonverbal IQ scores declined significantly. At the individual level, RCI indicated nine and 11 children showed a clinically significant decline in Full Scale IQ (FSIQ) and nonverbal IQ scores, respectively. Decline in FSIQ was related to a history of seizures whereas decline in nonverbal IQ was associated with higher initial IQ. Conclusion: Cognitive abilities in children with cerebral palsy evolve over time and selective deficits may not be observable until a later age, highlighting the importance of repeated cognitive assessment throughout childhood and adolescence.